2016
DOI: 10.1016/j.future.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Healing on the cloud: Secure cloud architecture for medical wireless sensor networks

Abstract: There has been a host of research works on wireless sensor networks (WSN) for medical applications. However, the major shortcoming of these efforts is a lack of consideration of data management. Indeed, the huge amount of high sensitive data generated and collected by medical sensor networks introduces several challenges that existing architectures cannot solve. These challenges include scalability, availability and security. Furthermore, WSNs for medical applications provide useful and real information about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(66 citation statements)
references
References 31 publications
0
65
0
1
Order By: Relevance
“…Lounis et al [8] proposed a new cloud-based architecture for medical wireless sensor networks and developed an access control that supports complex and dynamic security policies, which relies on ciphertext-policy attribute-based encryption (CP-ABE). Simulation results showed that their access control is efficient, fine-grained, and scalable.…”
Section: Access Controlmentioning
confidence: 99%
“…Lounis et al [8] proposed a new cloud-based architecture for medical wireless sensor networks and developed an access control that supports complex and dynamic security policies, which relies on ciphertext-policy attribute-based encryption (CP-ABE). Simulation results showed that their access control is efficient, fine-grained, and scalable.…”
Section: Access Controlmentioning
confidence: 99%
“…speech/voice, image, video etc.). Due to the elasticity, on-demand self-service, ubiquity, resource pooling, scalability of clouds in data acquisition, data storage, data analysis and data transmission [20], a cloud based healthcare system accessed by smart phones can be an effective solution for both patients and doctors.…”
Section: Cloud Computing In Healthcarementioning
confidence: 99%
“…Otherwise, patients may not be willing to share their health and social data such that the infection analysis would be disabled. In fact, attribute-based encryption (ABE) and identity-based broadcast encryption (IBBE) are widely adopted encryption algorithms [12]. Particularly, CP-ABE is conceptually closer to traditional access control models, to enforce fine-grained access control of encrypted data.…”
Section: Our Techniquesmentioning
confidence: 99%
“…The health cloud takes as input a health ciphertext CT ℎ and a heath reencryption key RK ℎ and outputs a reencrypted health ciphertext RT ℎ . (12) . (PK, SK, ID ).…”
Section: (9)mentioning
confidence: 99%